2007
DOI: 10.1002/ccd.20816
|View full text |Cite
|
Sign up to set email alerts
|

Coronary septal collaterals as an access for the retrograde approach in the percutaneous treatment of coronary chronic total occlusions

Abstract: Coronary septal collaterals can be used as an access for the retrograde approach in the percutaneous treatment of CTOs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
107
1
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 149 publications
(113 citation statements)
references
References 11 publications
1
107
1
4
Order By: Relevance
“…6) Moreover, novel devices and technique developments such as retrograde approach, contralateral injection, anchoring techniques, tapered-tip guidewires, and more flexible microcatheters have dramatically improved the success rates of the TR approach for CTOs. [7][8][9][10] A rare case of congenital anomalous coronary origin was found during coronary angiography (< 1%). TR PCI for a CTO without a stump in an RCA with a high anterior takeoff and downward course is one of the most technically challenging cases for interventionists.…”
Section: Discussionmentioning
confidence: 99%
“…6) Moreover, novel devices and technique developments such as retrograde approach, contralateral injection, anchoring techniques, tapered-tip guidewires, and more flexible microcatheters have dramatically improved the success rates of the TR approach for CTOs. [7][8][9][10] A rare case of congenital anomalous coronary origin was found during coronary angiography (< 1%). TR PCI for a CTO without a stump in an RCA with a high anterior takeoff and downward course is one of the most technically challenging cases for interventionists.…”
Section: Discussionmentioning
confidence: 99%
“…Retrograde approach has been described initially via the bypass grafts 20 and more recently the use of septal collaterals has been described 18 to be safe and effective. Retrograde approach for recanalization of CTO has gained popularity recently with improved success rates as shown in several case reports and small series of selected patients.…”
Section: Clinical Perspective See P 132mentioning
confidence: 99%
“…The technique of retrograde approach has evolved over time with accumulating experience and emergence of dedicated devices. We have previously described the use of septal CCs and technique of controlled antegrade and retrograde subintimal tracking (CART) 18,19 to facilitate this procedure.…”
Section: Retrograde Procedural Details Procedural Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…We reported that the prevalence of tapered pattern was significantly more frequent in distal lumen compared to proximal lumen (11). The utilization of retrograde approach is one of the main advances in revascularization techniques during CTO procedures and is responsible for the incremental success rates (6,20).…”
Section: Proximal and Distal Lumen Patternmentioning
confidence: 99%